Proceedings of the Sixth International Workshop on MobiArch 2011
DOI: 10.1145/1999916.1999921
|View full text |Cite
|
Sign up to set email alerts
|

Using predictable mobility patterns to support scalable and secure MANETs of handheld devices

Abstract: Mobile ad-hoc networks of wireless devices (MANETs) hold the promise of providing network services without traditional infrastructures that could fall victim to manipulation and censorship. Unfortunately, current MANET systems suffer significant scalability problems, effectively precluding their use for general-purpose networking. We suggest tailoring MANETs to particular classes of application and leveraging application-specific properties to increase scalability. This paper describes the design of a scalable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Understanding the impact of mobility patterns is also of relevance in the design of forwarding protocols. Bild et al [27] exploited the predictability of mobility patterns of people to improve the reliability and scalability of routing on Mobile Ad-Hoc Networks (MANETs). Scalability is important because most routing protocols do not scale to very large networks without traditional fixed infrastructures (obviously hard to be made available in hostile environments).…”
Section: Sensor Networkmentioning
confidence: 99%
“…Understanding the impact of mobility patterns is also of relevance in the design of forwarding protocols. Bild et al [27] exploited the predictability of mobility patterns of people to improve the reliability and scalability of routing on Mobile Ad-Hoc Networks (MANETs). Scalability is important because most routing protocols do not scale to very large networks without traditional fixed infrastructures (obviously hard to be made available in hostile environments).…”
Section: Sensor Networkmentioning
confidence: 99%
“…Mobility patterns and sensing. Previous studies have shown the benefits controlled (or predictable) mobility can have on sensing coverage and routing efficiency [21], [2], [3], [6], [28]. Reddy et al put forward a closely related idea leveraging participant's previous location traces to guide scheduling in participatory sensing campaigns [33].…”
Section: Related Workmentioning
confidence: 99%
“…(2) We describe the design ( § III) and implementation of a full CSC prototype and its integration in different example applications ( § IV). (3) We report real-world evaluation results of our ideas with 2 different applications, and example crowdsensing tasks to demonstrate the lowoverhead and high effectiveness of Crowd Soft Control ( § V).…”
Section: Introductionmentioning
confidence: 99%
“…Bild et al [13] exploited the predictability of mobility patterns of people to improve the reliability and scalability of routing on Mobile AdHoc Networks (MANETs). This is quite important because most routing protocols do not scale to very large networks without traditional fixed infrastructures which are hard to be made available in certain environments (battlefields for instance).…”
Section: A Sensor Networkmentioning
confidence: 99%